Joint Detailing Between Double Tee Bridge Girders for Improved Serviceability and Strength. Issue 1 (2016) - Wehbe, Nadim; Konrad, Michael; Breyfogle, Aaron
Precast, prestressed double tee bridge girders are widely used for accelerated bridge construction on local roads in South Dakota. A common issue among double tee bridges in South Dakota is the rapid deterioration of longitudinal joints (shear keyways) between adjacent girders. Deteriorated joints allow moisture and deicing chemicals to reach the deck reinforcement, which leads to premature corrosion of reinforcing steel and spalling of concrete. The structural performance of conventional and proposed longitudinal joints between precast double tee bridge girders was examined experimentally under cyclic and monotonic loading. The proposed continuous joint with overlapping steel mesh reinforcement in a grouted shear keyway exhibited serviceability and strength performance characteristics substantially improved over those of the conventional grouted joint with discrete welded connections.